Turning a green alga red: engineering astaxanthin biosynthesis by intragenic pseudogene revival in Chlamydomonas reinhardtii. Issue 10 (31st March 2020) - Perozeni, Federico; Cazzaniga, Stefano; Baier, Thomas; Zanoni, Francesca; Zoccatelli, Gianni; Lauersen, Kyle J.; Wobbe, Lutz; Ballottari, Matteo
Summary: The green alga Chlamydomonas reinhardtii does not synthesize high‐value ketocarotenoids like canthaxanthin and astaxanthin; however, a β‐carotene ketolase ( Cr BKT) can be found in its genome. Cr BKT is poorly expressed, contains a long C‐terminal extension not found in homologues and likely represents a pseudogene in this alga. Here, we used synthetic redesign of this gene to enable its constitutive overexpression from the nuclear genome of C. reinhardtii . Overexpression of the optimized Cr BKT extended native carotenoid biosynthesis to generate ketocarotenoids in the algal host causing noticeable changes the green algal colour to reddish‐brown. We found that up to 50% of native carotenoids could be converted into astaxanthin and more than 70% into other ketocarotenoids by robust Cr BKT overexpression. Modification of the carotenoid metabolism did not impair growth or biomass productivity of C. reinhardtii, even at high light intensities. Under different growth conditions, the best performing Cr BKT overexpression strain was found to reach ketocarotenoid productivities up to 4.3 mg/L/day. Astaxanthin productivity in engineered C. reinhardtii shown here might be competitive with that reported for Haematococcus lacustris (formerly pluvialis ) which is currently the main organism cultivated for industrial astaxanthin production. In addition, the extractability and bio‐accessibility of these pigments were much higher in cell wall‐deficient C. reinhardtii than the resting cysts of H. lacustris . Engineered C. reinhardtii strains could thus be a promising alternative to natural astaxanthin producing algal strains and may open the possibility of other tailor‐made pigments from this host.